The Role of Bacteria in the Pathogenesis and Progression of Idiopathic Pulmonary Fibrosis - Molyneaux, Phillip L.; Cox, Michael J.; Willis-Owen, Saffron A. G.; Mallia, Patrick; Russell, Kirsty E.; Russell, Anne-Marie; Murphy, Elissa; Johnston, Sebastian L.; Schwartz, David A.; Wells, Athol U.; Cookson, William O. C.; Maher, Toby M.; et al. (American journal of respiratory and critical care medicine, 2014)
Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease of unknown cause that leads to respiratory failure and death within 5 years of diagnosis. Overt respiratory infection and immunosuppression carry a high morbidity and mortality, and polymorphisms in genes related to epithelial integrity and host defense predispose to IPF. To investigate the role of bacteria in the pathogenesis and progression of IPF. We prospectively enrolled patients diagnosed with IPF according to international criteria together with healthy smokers, nonsmokers, and subjects with moderate chronic obstructive pulmonary disease as control subjects. Subjects underwent bronchoalveolar lavage (BAL), from which genomic DNA was isolated. The V3-V5 region of the bacterial 16S rRNA gene was amplified, allowing quantification of bacterial load and identification of communities by 16S rRNA quantitative polymerase chain reaction and pyrosequencing. Sixty-five patients with IPF had double the burden of bacteria in BAL fluid compared with 44 control subjects. Baseline bacterial burden predicted the rate of decline in lung volume and risk of death and associated independently with the rs35705950 polymorphism of the MUC5B mucin gene, a proven host susceptibility factor for IPF. Sequencing yielded 912,883 high-quality reads from all subjects. We identified Haemophilus, Streptococcus, Neisseria, and Veillonella spp. to be more abundant in cases than control subjects. Regression analyses indicated that these specific operational taxonomic units as well as bacterial burden associated independently with IPF. IPF is characterized by an increased bacterial burden in BAL that predicts decline in lung function and death. Trials of antimicrobial therapy are needed to determine if microbial burden is pathogenic in the disease.